Growth, Physiological, Hematological and Biochemical Responses of Growing Rabbits to Various Feeding Levels of Leucaena - Rohilla, P P; Bujarbaruah, K M; Kumar, M; Singh, G (Annals of Arid Zone, 2016)
Twenty rabbits. each of Ncw Zcaland White and Soviet Chinchilla breed. aged 12 week. were divided into four uniform groups. The first group was kept as control; in next three groups concentrate feed was substituted with 20. 40. and 60% leueaena leaves (on dry matter basis). Leucaena leaves after initial rejection were readily consumed within one week. Highest average daily weight gain was recorded ] 8.88Â±1.18 g under T, and the corresponding daily OM intake was 114.56Â±2.85 g. The treatment had a significant (1’<0.05) effect on growth. dry matter intake, haemoglobin. packed cell volume. red blood corpuscles. white blood corpuscles. mean cell volume. albumin. iron. cholesterol. urea. creatinine. calcium and phosphorus levels in the blood of rabbits. No acute. toxicity was observed during the experiment. however. rabbits under fourth group (T4) showed poor appetite. alopecia (loss of hair). depressed growth rate and dry matter intake. It was recommended that leueaena leaves may be added up to 40% level in rabbit diet. thereby minimizing the feed cost. Â